China's Slowdown and Rebalancing : Potential Growth and Poverty Impacts on Sub-Saharan Africa - Lakatos, Csilla; Maliszewska, Maryla; Osorio-Rodarte, Israel; Go, Delfin (World Bank, Washington, DC, 2016)
This paper explores the economic impacts of two related tracks of China's expected transformation—economic slowdown and rebalancing away from investment toward consumption—and estimates the spillovers for the rest of the world, with a special focus on Sub-Saharan African countries. The paper finds that an average annual slowdown of gross domestic product in China of 1 percent over 2016–30 is expected to result in a decline of gross domestic product in Sub-Saharan Africa by 1.1 percent and globally by 0.6 percent relative to the past trends scenario by 2030. However, if China's transformation also entails substantial rebalancing, the negative income effects of the economic slowdown could be offset by the positive changes brought along by rebalancing through higher overall imports by China and positive terms of trade effects for its trading partners. If global supply responds positively to the shifts in relative prices and the new sources of consumer demand from China, a substantial rebalancing in China could have an overall favorable impact on the global economy. Economic growth could turn positive and higher on average, by 6 percent in Sub-Saharan Africa and 5.5 percent globally, as compared with the past trends scenario. Finally, rebalancing reduces the prevalence of poverty in Sub-Saharan Africa compared with the isolated negative effects of China's slowdown, which slightly increase the incidence of poverty. Overall, China's slowdown and rebalancing combined are estimated to increase gross domestic product in Sub-Saharan Africa by 4.7 percent by 2030 and reduce poverty, but the extent of this varies by country.